Size fractionated primary production measurements from CTD Niskin samples collected along the Barents Sea cruise transect, JR17007 and JR18006 (ChAOS cruises). - Downes, Patrick; Dixon, Joanna (NERC EDS British Oceanographic Data Centre NOC, 2021)
Rates of net primary production were measured at six stations in the Barents Sea during the Changing Arctic Ocean cruises JR17007 (10th July - 5th August 2018) and JR18006 (29th June - 2nd August 2019), on board the RSS James Clark Ross. At each station, six light depths were sampled corresponding to photosynthetically active radiation (PAR) percentages (100%, 50%, 25%, 15%, 3%, 1%), calculated from the surface PAR (log). Samples were collected using a rosette sampler equipped with 24 Niskin bottles (20 L) to collect water at defined depths. Rates of net primary production were estimated using the 14C incorporation technique, according to Joint & Pomeroy (1993). Per depth, triplicate samples were dispensed into 60 mL acid washed polycarbonate bottles, inoculated with 370 kBq NaH14CO3 and incubated on-deck at simulated PAR depths for 24 hours. Simultaneous dark incubations were performed as well as background measurements (T0). Incubations were terminated by sequential filtering through 20, 2 and 0.2 μm polycarbonate filters (Millipore™). Filters were fumed with HCl (37%) for 2 hours and desiccated for 12 hours prior to counting using ProSafe FC+ liquid scintillation cocktail (Meridian Biotechnologies). After being stored in the dark for approximately 12 hours, filters were counted using a liquid scintillation counter (TriCarb 3100TR).